Coping in Teams: Exploring Athletes’ Communal Coping Strategies to Deal With Shared Stressors - Leprince, Chloé; D’Arripe-Longueville, Fabienne; Doron, Julie (Frontiers in Psychology, 2018)
Although sport psychology research has mainly focused on stress and coping as intrapersonal processes, stressful circumstances are often experienced in social groups and coping emerges as a combination of individual and group effort (Tamminen & Gaudreau, 2014). Based on Lyons, Mickelson, Sullivan and Coyne’s (1998) model of communal coping, this study aimed to address the lack of knowledge about stress and coping as an interpersonal process, by exploring shared stressors and communal coping strategies within team sports. Semi-structured interviews were conducted with 10 team sport athletes (seven males, three females; Mage = 26.3 years, SDage = 7.67, range 15-38) who participated in different team sports (football, rugby, volleyball, ice hockey, basketball). Data were analysed using an inductive thematic analytic procedure. The results revealed four themes of shared stressors involving issues relating to social pressure, relationships between teammates, performance, or logistics and organisation; and four themes of communal coping, namely: problem-focused communal efforts, relationship-focused coping, communal management of emotions, and communal goal withdrawal. The results provided empirical support to the communal coping model (Lyons et al., 1998) and extend understanding of coping processes as defined initially by the CMRT of emotion (Lazarus, 1999, 2000b). This study provided unique insight into the nature of communal coping in sport and performance setting, and specifically, how stressors are apprehended in team sports and how athletes can collaborate to deal with shared stressors during competitive encounters.